Biomimetic Acid Soil Amelioration using Indigenous Soil Isolates in Comparison to other Potential Microorganism. Issue 10 (30th May 2016) - Park, E.H.; Mahanty, B.; Yoon, S.U.; Kim, C.G.
ABSTRACT: In the present study, four different soil isolates were screened and evaluated for their acid neutralization capacity in liquid culture and soil column tests with either artificial soil or real acid soil. Miniaturized artificial soil column tests using Aspergillus fumigatus, Aureobasidium pullulans, and Myxococcus xanthus were also included. In the liquid-phase experiment, two isolates (designated 'A' and 'B') effectively increased the medium pH from 4 to 6.74 and 6.53, respectively, during the 6 d, and the ammonium-nitrogen (NH4 + -N) concentration increased from 400 ppm to 1000 ppm (isolate A). The isolates A and B were identified as Enterococcus hirae and Clostridium sp. in 16S ribosomal ribonucleic acid (rRNA) analysis. Artificial soil pH increased more quickly with soil isolates than in comparison to A. fumigatus or A. pullulans . In real acid soil pH increased from 4.2 to about pH 6.5 within 4 d. This suggests that biomimetic approaches could be valuable for acid soil amelioration.